El juego simbólico en la inteligencia emocional de los niños de educación inicial subnivel 2 de la escuela de educación básica Jesús Infante ciudad de Riobamba - Gavilanes Ortiz, Joseline Esmeralda (2025)
Emotional intelligence, defined as the ability to recognize, understand, regulate, and express one's own and others' emotions, plays a crucial role in developing social skills, building healthy interpersonal relationships, and assertive conflict resolution. This research aimed to analyze the influence ofsymbolic play on the development ofemotional intelligence in children in early childhood education (sublevel 2) at Jests Infante Elementary School in Riobamba. A mixedmethods approach was used in this research, allowing for a comprehensive understanding of the impact of symbolic play on children's emotional intelligence in early childhood education (sublevel 2). The observation technique was used to systematically record children's interactions and behaviors during symbolic play, and the observation sheet was used to structurally record these behaviors. The study population consisted of 43 children from the initial level 2 classes A and B of Jesüs Infante Basic Education School in Riobamba City. Only children from class A, which consists of 24 children, were selected, as this group has been identified as the most suitable for analyzing symbolic play and its impact on emotional intelligence. In conclusion, this type of play not only stimulates imagination and creative thinking but is also closely linked to emotional development, reflecting significant progress in skills such as empathy, self-regulation, and emotional expression. Cases where these competencies are still developing were also identified, which is art of the natural rocess of child develo ment